2021
DOI: 10.1038/s41598-021-91914-9
|View full text |Cite
|
Sign up to set email alerts
|

Species variations in tenocytes’ response to inflammation require careful selection of animal models for tendon research

Abstract: For research on tendon injury, many different animal models are utilized; however, the extent to which these species simulate the clinical condition and disease pathophysiology has not yet been critically evaluated. Considering the importance of inflammation in tendon disease, this study compared the cellular and molecular features of inflammation in tenocytes of humans and four common model species (mouse, rat, sheep, and horse). While mouse and rat tenocytes most closely equalled human tenocytes’ low prolife… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 129 publications
0
19
1
Order By: Relevance
“…Horses had the shortest Mahalanobis distance to humans in terms of matrix remodelling proteinases, suggesting that horses are most suitable for assessing ECM production and tendon healing. However, rat tenocytes best resembled humans in terms of inflammatory mediators; furthermore, under healthy conditions, rat tenocytes had the shortest Mahalanobis distance with regards to overall gene expression [126], bringing into question Hurtig et al's proposition that large animals have more similar properties to humans.…”
Section: Animal Models Of Tendon/ligament Injurymentioning
confidence: 82%
See 1 more Smart Citation
“…Horses had the shortest Mahalanobis distance to humans in terms of matrix remodelling proteinases, suggesting that horses are most suitable for assessing ECM production and tendon healing. However, rat tenocytes best resembled humans in terms of inflammatory mediators; furthermore, under healthy conditions, rat tenocytes had the shortest Mahalanobis distance with regards to overall gene expression [126], bringing into question Hurtig et al's proposition that large animals have more similar properties to humans.…”
Section: Animal Models Of Tendon/ligament Injurymentioning
confidence: 82%
“…It is accepted that no one animal model of tendon or ligament injury can perfectly replicate human pathology. Oreff et al calculated the Mahalanobis distances, a nondimensional measure of dissimilarity, of four model species to humans: mouse, rat, horse, and sheep, and found that the species that best matched humans depended on which functional group of genes were analysed [126]. Horses had the shortest Mahalanobis distance to humans in terms of matrix remodelling proteinases, suggesting that horses are most suitable for assessing ECM production and tendon healing.…”
Section: Animal Models Of Tendon/ligament Injurymentioning
confidence: 99%
“…In all tendons, applying galvanic current application was found to have a similar clinical benefit, but we cannot rule out the fact that the calcaneal tendon of mice would present a different response to galvanic current. In fact, different species have been reported to have different inflammatory tenocyte responses (Oreff et al, 2021), and although mice and humans present high overall similarities in their tenocyte responses (Oreff et al, 2021), it is necessary to apply galvanic current in the presence of specific NLRP3 blockers, such as MCC950, in additional animal models with species other than mice.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, combinatory effects of loading and culture conditions on inflammatory responses needs to be explored. Determining inflammatory effects in vitro is also further complicated by tenocyte response variations associated with the model species used (Oreff et al, 2021), which indicates the importance of selecting a model that most appropriately matches the research question.…”
Section: Injured Mouse Achilles Tendon Tpcsmentioning
confidence: 99%